Pengawasan Pelaksanaan Otonomi Daerah - Mhd Ansori (Wajah Hukum, 2018)
Supervision is a part of the overall authority of the government, because at the last level the Central Government must be responsible for the whole administration, justifying the holding of supervision of all regional actions, because the integrity of the Unitary State must be maintained. Regional autonomy as autonomy for regional people and not "regional" autonomy in the sense of a particular region / territorial at the local level, if the implementation of regional autonomy is carried out by the Regional Government, that authority must be managed fairly, honestly and democratically. In administering the government, the central government uses the principles of decentralization, co-administration and deconcentration in accordance with the prevailing laws and regulations, while the regional governments in administering the government use the principles of decentralization and co-administration. The purpose of this paper is to find out, analyze the supervision of regional autonomy. The type of research used is normative juridical research, using a conceptual approach, a legislative approach and a historical approach.